1986
DOI: 10.1093/oxfordjournals.jbchem.a135549
|View full text |Cite
|
Sign up to set email alerts
|

A cDNA Clone Used to Study mRNA Inducible in Human Tonsillar Lymphocytes by a Tumor Promoter1

Abstract: A cDNA clone inducible by either a tumor promoter, 12-o-tetradecanoyl phorbol-13-acetate (TPA), or a T-cell mitogen, phytohemagglutinin (PHA), was isolated from a cDNA library constructed from the poly(A) + RNAs of TPA- and PHA-stimulated human tonsillar lymphocytes, and was named pLD78. Stimulation of the tonsillar lymphocytes with either TPA or PHA increased the amount of pLD78-specific RNA by about 10-fold, and simultaneous stimulation with TPA and PHA, by at least 30-fold. Analysis of the pLD78 cDNA sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
57
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(60 citation statements)
references
References 0 publications
3
57
0
Order By: Relevance
“…RANTES: deduced from cDNA cloned from antigen or mitogen-stimulated human T cell lines [21]. pLD78: from stimulated human tonsillar lymphocytes [22]. TCA 3: from ConA-stimulated mouse T cell line [23].…”
Section: Resultsmentioning
confidence: 99%
“…RANTES: deduced from cDNA cloned from antigen or mitogen-stimulated human T cell lines [21]. pLD78: from stimulated human tonsillar lymphocytes [22]. TCA 3: from ConA-stimulated mouse T cell line [23].…”
Section: Resultsmentioning
confidence: 99%
“…S ;D1 0014-5793(95)01235-4 (reverse primer) 5' CAACTGGTAATGGTAGCGAC) for 30 cycles of 95°C for 2 min, 55°C for 2 min and 72°C for 5 min in a Techne PHC-2 thermal cycler. One tenth of the reaction mixture was then subjected to a 2nd round of PCR in a 100¢tl reaction now containing 1 ¢tM each of either RANTES specific primers (forward primer 5' CCATGAAG-GTCTCCGCGGCAC reverse primer 5' CCTAGCTCATCTCCAA-AGAG antisense) based on the published RANTES cDNA coding sequence [12] or MIP-lc~ specific primers [13] (forward primer 5' AT-GCAGGTCTCCACTGCTGC and reverse primer 5' TCAGGCACT-CAGCTCCAGGTG) for 30 cycles of 95°C for 2 min, 55°C for 2 min and 72°C for 5 min. PCR products were visualized on 3% Nu-Sieve (FMC) agarose gels stained with 0.5 mg/ml ethidium bromide.…”
Section: Chemokine Cloning and Expressionmentioning
confidence: 99%
“…Similarly, as mentioned above, SCI/MIP-lI mRNA is super-induced during endotoxin (lipopolysacharride, LPS) stimulation of murine macrophages (Davatelis et al, 1988), and is super-induced in human T-cell lines by phorbol esters (PMA) and/or PHA and cyclohexamide (Obaru et al, 1986;Yamamura et al, 1989;Blum et al, 1990). Interestingly, a basal level of SCI/MIP-lac mRNA is detected in unstimulated cultured murine macrophage Davatelis et al, 1988) and mast cell lines (Gordon et al, 1990, and M.P. unpublished results), whereas it is undetectable in unstimulated human monocyte (U937) and T-cell (Jurkat) lines although it can be induced by PHA and/or PMA (Obaru et al, 1986;Yamamura et al, 1989;Blum et al, 1990).…”
mentioning
confidence: 81%
“…Although it is unlikely that the SCI/MIP-la gene is itself directly involved in the cellular transformation process, nearby genetic lesions which activate proto-oncogenes or inactive suppressor genes may also coincidentally lead to aberrant SCI/MIP-la gene expression. The up-regulation of SCI/MIP-Ia gene expression has been detected in the peripheral blood of a number of ANLL and ALL patients (Yamamura et al, 1989) (Lord & Wright, 1980) and monocytes (Pojda et (Yamamura et al, 1989) and mast cells (Gordon et al, 1990 (Davatelis et al, 1988) and human (Forsdyke, 1985;Obaru et al, 1986;Zipfel et al, 1989) SCI/MIP-lI cDNAs revealed a number of conserved (TATTT) motifs in the 3' untranslated region of the mRNA which have been implicated in the modulation of mRNA stability of a number of other cytokine mRNAs (Caput et al, 1986;Shaw & Kamen, 1986). Similarly, as mentioned above, SCI/MIP-lI mRNA is super-induced during endotoxin (lipopolysacharride, LPS) stimulation of murine macrophages (Davatelis et al, 1988), and is super-induced in human T-cell lines by phorbol esters (PMA) and/or PHA and cyclohexamide (Obaru et al, 1986;Yamamura et al, 1989;Blum et al, 1990).…”
mentioning
confidence: 99%
See 1 more Smart Citation